Literature Review Of Drug-Receptor Interactions Based On Molecular Docking From The Perspective Of Lock And Key Theory - Saeful Amin Saeful Amin; Nazmie Nurtsalis; Dina Sumida Rosydiana; Andra Nadya Hidayat (International Journal of Health Engineering and Technology, 2026)
Drug-receptor interactions are the primary basis for determining the effectiveness of a therapy. Understanding the mechanisms of these interactions continues to evolve with advances in computational technology, one of which is through the molecular docking approach. This method enables in silico analysis of ligand-receptor interactions, including predictions of binding affinity, complex stability, and the types of molecular interactions that occur. Furthermore, the lock and key theory is a fundamental concept in explaining the structural compatibility between drugs and receptors, which influences bond strength and specificity. The method used in this review is a literature review from various scientific databases such as PubMed, Google Scholar, and ScienceDirect, with journals published in 2020 or later as inclusion criteria. The results show that oseltamivir has high affinity for neuraminidase through specific interactions such as hydrogen bonding and electrostatic binding. However, mutations in the receptor can lead to drug resistance. Therefore, understanding the mechanisms of molecular interactions is crucial for the development of more effective antiviral drugs.